Medical treatment of gastroesophageal reflux disease - Bor, Serhat; Kalkan, İsmail Hakkı (Turkish Journal of Gastroenterology, 2017)
Abstract Proton pump inhibitors (PPIs) are the most effective agents in the first-line and maintenance treatment of gastroesophageal reflux disease. As the grade of esophagitis increases, an increase is also observed in the level of endoscopic response to PPIs. In the first-line therapy of patients with severe esophagitis (Los Angeles (LA) Grade C-D), administration of a standard dose of PPIs bid has been reported to be more beneficial than PPIs qd. While any intermittant and low dose-continuous treatment can be chosen for the maintenance therapy of patients with non-erosive reflux disease or mild esophagitis (LA Grade A-B), continuous use of a standard dose of PPIs is preferred in the maintenance therapy of patients with severe esophagitis (LA Grade C-D). In patients who use PPIs for a long time, the drug must be stopped by gradually decreasing the dose. Cite this article as: Bor S, Kalkan İH. Medical treatment of gastroesophageal reflux disease. Turk J Gastroenterol 2017;28(Suppl 1); S48-S52 Full Text Turkish